Unity and disunity in Japanese modern times: the songs and theories of Yamada Kо̄saku - Watson, FK (2020)
This thesis examines the work of Yamada Kōsaku 山田耕筰 (1886-1965), a Japanese composer in the Western classical tradition. Scholarship to date has tended to ascribe to Yamada a substantial change in his identity, whereby his recognition of his Japanese nationality sometime before 1920 brought his music to its laudable maturity. I argue that this is a misinterpretation. Instead, any such shift was superficial, only rhetorical in nature, and overlaid a stable philosophical core. This philosophy can be defined as a modernist faith in totalizing unity.